2021
DOI: 10.3390/children8010037
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Management of Type 2 Diabetes in Youth

Abstract: The prevalence of type 2 diabetes mellitus (T2DM) in children and adolescents is on the rise, and the increase in prevalence of this disorder parallels the modern epidemic of childhood obesity worldwide. T2DM affects primarily post-pubertal adolescents from ethnic/racial minorities and those from socioeconomically disadvantaged backgrounds. Youth with T2DM often have additional cardiovascular risk factors at diagnosis. T2DM in youth is more progressive in comparison to adult onset T2DM and shows lower rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…For obese children, probiotics may work by promoting lipid metabolism, increasing GLP-1 secretion, raising leptin levels and regulating intestinal flora homeostasis. Firstly, several studies have shown that GLP-1 agonists (e.g., liraglutide) could be effective for weight loss in pediatric patients [71,72]. In our systematic review, probiotics were found to increase GLP-1 secretion in vivo, which is essential for promoting insulin secretion through the action of intestinal proinsulin.…”
Section: Discussionmentioning
confidence: 84%
“…For obese children, probiotics may work by promoting lipid metabolism, increasing GLP-1 secretion, raising leptin levels and regulating intestinal flora homeostasis. Firstly, several studies have shown that GLP-1 agonists (e.g., liraglutide) could be effective for weight loss in pediatric patients [71,72]. In our systematic review, probiotics were found to increase GLP-1 secretion in vivo, which is essential for promoting insulin secretion through the action of intestinal proinsulin.…”
Section: Discussionmentioning
confidence: 84%
“…Metformin, a biguanide, represents the first-choice medication. It is administered orally and acts to reduce glucose levels, inhibiting the process of hepatic gluconeogenesis and promoting intestinal absorption of glucose [ 47 , 48 , 49 ]. Although metformin does not often result in significant body weight loss, it appears to prevent or delay alteration of glucose homeostasis in children at high risk of developing type 2 diabetes mellitus [ 50 ].…”
Section: Obesity Cardiometabolic Complications and Medical Treatmentmentioning
confidence: 99%
“…15,16 Currently, several synthetic antidiabetic drugs are available to lower blood glucose level: metformin, sulfonylureas, meglitinides, thiazolidinediones, dipeptidyl peptidase-4 inhibitors, glucagon-like peptide-1 receptor agonists, and sodium− glucose cotransporter-2 inhibitors. 17,18 Natural products and traditional herbal medicines also have potential antidiabetic efficacy. 19−21 Naturally occurring chemical compounds in plants, called phytoconstituents, can inhibit α-amylase and be used to manage blood glucose level in T2DM with fewer side effects than those caused by synthetic agents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Currently, several synthetic antidiabetic drugs are available to lower blood glucose level: metformin, sulfonylureas, meglitinides, thiazolidinediones, dipeptidyl peptidase-4 inhibitors, glucagon-like peptide-1 receptor agonists, and sodium–glucose cotransporter-2 inhibitors. , …”
Section: Introductionmentioning
confidence: 99%